Personalized acupuncture treatment with Sasang typology - Chae, Han; Lee, Jeongyun; Jeon, Eun Sang; Kim, Jae Kyu (Elsevier, 2017)
The Sasang typology, traditional Korean personalized medicine, divides people into four Sasang types and suggests type-specific medical herbs and acupuncture for more safe and effective treatment. The main idea of Sasang typology seems relatively simple; however, the Sasang type diagnosis and type-specific treatment in clinical situation has been difficult for the clinicians and researchers. This study provided clinical procedures of type-specific Tae-Geuk Acupuncture (TGA) therapy along with basic understandings on Sasang typology and clinical indices for Sasang type differentiation. The TGA therapy would be useful for psychosomatic complaints and chronic pains by restoring the balance of Yin-Yang. The clinical application of TGA, its related biological mechanisms, and implications for further prospective clinical study were discussed. (C) 2017 Korea Institute of Oriental Medicine. Published by Elsevier. This is an open access article under the CC BY-NC-ND license.
Keywords: Differential Diagnosis; Personalized Acupuncture; Sasang Typology; Tae-Geuk Acupuncture